THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL JUSTICE ON EMPLOYEE PERFORMANCE AT PT BANK SULSELBAR PALOPO - Nurul Izza, Mifta; Haedar, Haedar; Hadis Badewi, Muhammad (Universitas Islam Lamongan, 2025)
This study aims to analyze the influence of transformational leadership and organizational justice on employee performance at PT. Bank Sulselbar Palopo, as well as the interaction of both in influencing employee productivity. Using a quantitative approach and multiple linear regression analysis techniques, this study involved 50 employees as samples, taken through census sampling techniques. Transformational leadership and organizational justice have a significant positive influence on employee performance, with both creating a better work environment, increasing employee satisfaction, motivation, and productivity.